Redesign Corporate Identity Sebagai Peningkatan Image Perusahaan Studi Kasus PT. Finansia Multi Finance - Ari Saputra; Ade Kosasih; Deden Bagja Sudrajat (UNIVERSITAS RAHARJA, 2016)
The era of globalization brings two effects, on the one hand can increase the opportunities in the field of employment, on the other side of the business world increasingly keen competition and tight. Therefore, it needs the right strategy for success in the business world. In marketing the product until now the company has been using various forms of media support facilities include: media banners, xbanner, brochures, stickers products and supported other visual media used by the company. But the company realized that a competitor with a similar type of business more and more, and also continues to grow. The problems increase with the identity of the old logo is not in accordance with the vision and mission as well as management targets. From the condition the company calls for the renewal of the corporate identity to build the image and identity is formed through the overall appearance of design in any media promotional campaign as a support program in order to further enhance the attractiveness to prospective customers. Analysis of problems derived from interviews with Branch Operation Manager PT. Finansia Multi Finance relating to the design of corporite identity redesign. The end result of this research is the manufacture of Graphic Standards Manual that is intended for the manufacture of the logo as a corporate identity of a company systematically arranged, and there is no error of perception / view in the application of the logo on any existing media include media banners, xbanner, brochures, stickers products and supported other visual media used by the company. With the redesign of the design coorporite identity at PT. Finansia Multi Finance, is expected to reinforce the existence and increase consumer purchasing power against PT. Finansia Multi Finance itself.